Implementasi Model Pembelajaran Discovery Learning untuk Meningkatkan Keaktifan Berpikir Kritis Siswa dalam Mata Pelajaran PPKn di SMKN 2 Maros - Yulfa Lumbaa; Nur Alifia; Fahiratun Afiat Muizunzila; Lukman Ismail; Abdul Azis; Sakattang Sakattang (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2023)
This research aims to increase students' active critical thinking in Civics Learning by implementing the Discovery Learning Learning Model. The subjects in this research were class X DKV students at SMKN 2 Maros with a total of 34 students, consisting of 21 male students and 13 female students. The research method used in this research is Kemmis and Mc Taggart using a classroom action research design consisting of two cycles. In this research, it is a multiple choice test which is carried out at the end of the cycle. The results of this research show that student learning outcomes in cycle I obtained an average score of 60 and an average percentage score of 60%, while classical completeness was 60% in the sufficient category and continued in the next cycle in the second cycle actions obtained an average of 83 .0, the average percentage score of 83.0% with classical completeness of 90% is in the very good category. The results of the data in cycle II activities have met the KKM which has been determined by student learning outcomes in PPKn learning obtained in cycle I and cycle II, showing that there has been an average increase of 30%. Based on the research results, it can be concluded that the application of the Discovery Learning learning model can increase active critical thinking in PPKn learning for class X DKV students at SMKN 2 Maros for the 2023/2024 academic year.